ANALISIS KARAKTER QARUN DALAM QS AL-QASAS AYAT 76-83 PERSPEKTIF TAFSIR MAQĀṢIDI - Milhatina Umi Haidaroh; Ikhwanuddin; Muhammad Nur Amin (LPPM Institut Daarul Qur'an Jakarta, Indonesia, 2025)
The story of Qarun in Surah Al-Qasas (verses 76–83) contains profound moral lessons about the importance of gratitude for the blessings bestowed by Allah SWT. Qarun was a man granted immense wealth, yet he fell into arrogance, excessive love for worldly pleasures, and denial of Allah as the true source of his prosperity. As a result, he was destroyed—a fate that serves as a timeless warning for humanity. This study employs a tafsīr maqāṣidī (maqāṣid-based interpretation) approach to analyze Qarun’s character and the underlying Islamic legal values found in his story. This method emphasizes exploring the noble objectives of divine revelation, particularly three key aspects of maqāṣid al-sharīʿah: ḥifẓ al-dīn (preservation of religion), ḥifẓ al-nafs (preservation of life), and ḥifẓ al-māl (preservation of wealth). Qarun stands as a clear example of failure to uphold these values due to greed and pride. The story also highlights the principle of al-musāwah (equality), affirming that wealth and status are not measures of a person’s virtue in the sight of Allah—piety is. This message challenges the materialistic worldview that equates success with possessions. In today’s context, Qarun’s story is highly relevant as a critique of hedonism, consumerism, and social inequality. Qarun symbolizes moral collapse due to spiritual negligence and serves as a warning to manage worldly blessings ethically, responsibly, and in balance with both worldly and spiritual needs.